Combined economic-emission load dispatch solution using firefly algorithm and fuzzy approach - M. N. Abdullah; N. A. Abdullah; N. F. Aswan; S. A. Jumaat; N. H. Radzi; Ahmad Fateh Mohamad Nor (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
This paper proposes Firefly Algorithm (FA) with fuzzy approach for solving combined economic-emission load dispatch (CEELD) problem in power generation. The main objective of the CEELD problem is to determine the optimal cost and emission level of power generation and fulfill the load demand and operational constraints. The CEELD problem used weighted sum method to combine two objective functions (cost and emission) into single objective. Then, the Fuzzy-based mechanism approach is integrated in FA to find the best compromise solution for both conflicting cost and emission level. The FA has been tested on IEEE 118-bus 14-unit test system for minimization both cost of power generation and emission level. The performance of FA for solving CEELD problem has been investigated in terms of optimal solution, convergence characteristics and Pareto front solution. From the comparison of the CEELD solutions, it found that FA can provide significant cost and emission reduction compared to other methods. Thus, it can be used as alternative approach for solving any optimization problems.